RESEARCH OF A STRESS-STRAIN STATE OF POLYIMIDIC INTERCONNECTION STRUCTURES ON FLEXIBLE PRINTED CIRCUIT BOARD - Невлюдов, Ігор Шакирович; Палагін, Віктор Андрійович; Демська, Наталія Павлівна; Невлюдова, Вікторія Валеріївна; Стародубцев, Микола Григорович (Problems of Friction and Wear, 2019)
The most dangerous type of influences on flexible cables and printed circuit boards are elastic-plastic bending deformations or multicycle wearnes. These deformations occur between particles of the structure that rotate or oscillate relative to one another. The subject of this study is a flexible two-layer printed circuit board. The purpose of this work is to study the dependence of the parameters of durability of polyamide plugs with copper conductors on structural and technological solutions of two-layer structures and to develop recommendations for increasing the durability and stability of flexible structures of products of microelectronics and microelectromechanical systems. To achieve the goal, the following tasks need to be addressed: analysis of data on the influence of constructive and technological factors on the stress-strain state; conducting of modeling and engineering analysis of flexible printed circuit board power temperature influence; consideration of new structural and technological options for increasing the durability and durability of flexible structures; the establishment of the most important factors of strength. In solving the tasks, the methodology of modeling using CAD system Solid Works and finite elements method was used. Estimations is carried out using the Coffin-Manson criterion, which establishes the quadratic dependence of stability on the radius of the printed circuit board. As a result of the study, the distribution of normal stresses, forces and bending moments in copper and polyimide layers for different dimensions of the elements is calculated and compared. The results are presented in the form of a diagram of normal stress along the longitudinal axis. It was established that the use of protective polyamide layers increases durability of copper conductor in 1,8 ... 2,55 times. Diagrams of voltage distribution are presented in the form of color thermograms, and the estimated strength reserves were 2 ... 5 times. The obtained results show favorable conditions for achieving high quality of manufacturing of flexible copper-polyimide cables and printed circuit boards of integrated microelectronic devices.